A holonic metamodel for product traceability in Product Lifecycle Management. (17th December 2007) - Terzi, Sergio; Panetto, Herve; Morel, Gerard; Garetti, Marco
Product and production management have become complex processes, where more problems are overlapping each other, while the product development might ever take more into account the improved customers' tastes and requests in a shorter time-to-market. The Product Lifecycle and its related Management (PLM) are becoming unavoidable key aspects, creating such a 'product centric' problem. The integrated management of all the information regarding the product is one of the related questions. One of the main issues concerning with the product management in a wider perspective, deals with the traceability of the product itself. The present paper aims at discussing the question of PLM as a question of product traceability. The product traceability problem concerns with the management of the identification of a product along its lifecycle. The paper aims at discussing an innovative approach to product traceability, based on a holonic definition of the product and its lifecycle. The paper presents a reference metamodel where a 'product holon' is defined – in a whole lifecycle – as a single element, able to merge product's physical part with product information needed for tracing its life.